Liquefaction behaviour of twelve tropical hardwood species in phenol - Anil Kumar; Anil Sethy; Shakti Chauhan (Maderas: Ciencia y Tecnología, 2018)
Liquefaction of  ligno-cellulosic biomass is one of the chemical conversion technologies for developing new materials, adhesives and energy systems. The liquefaction process also provides an opportunity to utilize  ligno–cellulosic wastes such as saw-dust, woody wastes, branches and twigs, agro-residues, etc. for the development of value added products.  This paper presents the liquefaction behaviour of wood meal of twelve tropical hardwood species in phenol as liquefying media to produce chemically active liquid which has potential to be used as a raw material for developing different products. The liquefaction was carried out at 1400C temperatures for 120 minutes at different liquid  ratios. In all the cases, a viscous and sticky black liquid was obtained after the stipulated reaction time. The liquefaction efficiency was found to vary with species  and liquid ratio. The highest liquefaction efficiency of 93% was achieved in balsa wood at 1:3 (wood: phenol) liquid ratio. The liquefied wood and residues were characterized by FTIR spectroscopy. The liquefied wood was found to be highly acidic in nature. Viscosity of liquefied wood at higher liquid ratio was independent of wood species.  Correlation analysis revealed a strong negative relationship between wood basic density and liquefaction efficiency.